Significance of calcium: its correlation with red and white muscle contraction, fatigue and potential - Castro, Alejandra A.; Perez, Mariano B. L.; Gonzalez, Guillermo A.; Bonilla, Natalia C.; Santiago, Gerardo G.; Singh, Ishmeet (International Journal of Research in Medical Sciences, 2024)
According to the predominant types of muscle fibers in an individual, they will have the ability to perform different types of exercises (both aerobic and anaerobic). To comprehend the mechanism of muscle fibers, which can act in diverse ways, enhancing either resistance or power, it is essential to examine the significance of calcium. Calcium plays a crucial role in both red and white muscle fibers. The release of calcium in white (fast-twitch) muscle fibers is significantly greater and faster, resulting in increased energy consumption, facilitating explosive physical activities. Conversely, in red (slow-twitch) muscle fibers, the release of calcium occurs in smaller amounts and over a prolonged period, leading to sustained energy consumption. The characteristics of contraction in red fibers enable endurance activities. A reduction in the amount of calcium results in diminished muscle contractile capacity, known as fatigue. The primary contributing factor, as previously mentioned, is the decline in calcium, but factors such as lactic acid and the dephosphorylation of the myosin head also contribute to its onset.